2021
DOI: 10.3171/2020.12.focus20959
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis of women in neurosurgery: a Canadian perspective

Abstract: OBJECTIVEAlthough the past decades have seen a steady increase of women in medicine in general, women continue to represent a minority of the physician-training staff and workforce in neurosurgery in Canada and worldwide. As such, the aim of this study was to analyze the experiences of women faculty practicing neurosurgery across Canada to better understand and address the factors contributing to this disparity.METHODSA historical, cross-sectional, and mixed-method analysis of survey responses was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Neurosurgical workforce data were obtained for 210 nations through 42 included sources ( Supplemental Digital Content 2, Supplemental Table 1 , http://links.lww.com/NEU/E46). 1,17,18,22-61 A world map denoting total neurosurgeons per capita is shown in Figure 1. The color scale denotes countries in green if they have at least 1 neurosurgeon per 200 000 population as this has been described as the minimum requirement for essential neurosurgical workforce to address neurotrauma in low- and middle-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Neurosurgical workforce data were obtained for 210 nations through 42 included sources ( Supplemental Digital Content 2, Supplemental Table 1 , http://links.lww.com/NEU/E46). 1,17,18,22-61 A world map denoting total neurosurgeons per capita is shown in Figure 1. The color scale denotes countries in green if they have at least 1 neurosurgeon per 200 000 population as this has been described as the minimum requirement for essential neurosurgical workforce to address neurotrauma in low- and middle-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…Veilleux et al observed a similar trend at the Université de Montréal and Université Laval in their neurosurgery faculties and attributed this to cultures around staff recruitment at these institutions. 23 However, leadership among Canadian ophthalmology programs may be trending towards greater representation of women, considering that 4 out of Canada’s 15 centres (26%) currently have female Chairs.…”
Section: Discussionmentioning
confidence: 99%
“…There were 8 survey studies in the category of Diversity and Gender, all of which were focused on women in neurosurgery. [179][180][181][182][183][184][185][186] Several articles discussed the history of women in neurosurgery. [187][188][189] Lawson McLean and Johnson et al performed different analyses evaluating the representation of women neurosurgeons at national meetings in Germany and the United States.…”
Section: Diversity and Gendermentioning
confidence: 99%